Deep inferior epigastric artery as a collateral pathway to the lower extremities: A case report. (June 2022) - Tada, Kaoru; Murai, Atsuro; Nakamura, Yuta; Suganuma, Seigo; Tsuchiya, Hiroyuki
Summary: We describe a patient in whom the deep inferior epigastric artery served as a collateral pathway to the lower extremities, and free latissimus dorsi myocutaneous flap transfer was successfully used for reconstruction instead of the originally planned free rectus abdominis myocutaneous flap. A 74-year-old woman underwent subtotal tongue resection, followed by free flap tongue reconstruction for tongue cancer. Reconstruction using a free rectus abdominis myocutaneous flap was considered; however, preoperative contrast-enhanced computed tomography revealed complete occlusion of the bilateral external iliac arteries. Doppler ultrasonography revealed retrograde blood flow via the deep inferior epigastric artery, and the internal thoracic artery-deep inferior epigastric artery pathway served as a collateral pathway that supplied the lower extremities. The patient underwent reconstructive surgery using a free latissimus dorsi myocutaneous flap, and the flap completely survived. The internal thoracic artery-deep inferior epigastric artery pathway serves as a critical collateral pathway to the lower extremities in patients with aortoiliac occlusive disease. Blockage of the deep inferior epigastric artery in patients in whom this vessel shows retrograde blood flow may result in lower extremity ischemia. Therefore, preoperative Doppler ultrasonography is warranted to confirm the direction of the blood flow, in addition to evaluation of the deep inferior epigastric artery and its perforators before planning rectus abdominis myocutaneous flap or deep inferior epigastric artery perforator flap surgery.